2019
DOI: 10.7759/cureus.4578
|View full text |Cite
|
Sign up to set email alerts
|

International Survey of Physicians’ Perspectives on Percutaneous Endoscopic Gastrostomy Tube Feeding in Patients with Dementia and Review of Literature

Abstract: Percutaneous endoscopic gastrostomy (PEG) tube often remains to be used as a primary modality for feeding in patients with advanced dementia, perhaps due to misconceptions regarding the outcomes. Physicians' perceptions regarding the PEG tubes could be a significant contributing factor globally. A multidisciplinary approach involving the ethics committee can help address the issue. Our survey is focused on gauging physicians' perceptions regarding PEG tube utilization and its global impact on outcomes in demen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This reflects the growing recognition of the importance and benefits of PEG feeding among Egyptian neurologists, as we mentioned lately. This experience is globally adopted by neurologists and has been studied in some other studies over the last 20 years [17,18,22,26,28]. Similarly, they reported a very satisfactory experience to the caregivers in over half (52.3%) of the cases they referred to perform PEG.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This reflects the growing recognition of the importance and benefits of PEG feeding among Egyptian neurologists, as we mentioned lately. This experience is globally adopted by neurologists and has been studied in some other studies over the last 20 years [17,18,22,26,28]. Similarly, they reported a very satisfactory experience to the caregivers in over half (52.3%) of the cases they referred to perform PEG.…”
Section: Discussionmentioning
confidence: 71%
“…Out of total 174 responses, 53.5% attributed to either family resistance or financial reasons as the main barrier against performing PEG to the indicated patients. A recent international study in 2019 revealed a relatively higher percentage regarding these barriers reaching more than 75% of the cases [22]. The family usually goes against PEG for the mistaken idea about the PEG feeding is burdensome or even dangerous to apply, fearing of the surgical procedure itself, or the inability to handle and provide proper care, or altering body image [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown at this time if this is a result of cultural differences, disparities in health care access, or discrepancies in physician communication. Physician misperceptions regarding the utility of PEG tubes are also often a contributing factor to the overuse of PEG tubes in patients with dementia despite evidence to the contrary (49,50).…”
Section: Dementiamentioning
confidence: 99%